2020
DOI: 10.1016/j.chom.2019.10.022
|View full text |Cite|
|
Sign up to set email alerts
|

A Bioinformatic Analysis of Integrative Mobile Genetic Elements Highlights Their Role in Bacterial Adaptation

Abstract: Highlights d Introduces MGEfinder, a bioinformatic toolbox to detect MGE integrations d Describes the MGE repertoire, from small repeats to prophages, of 9 pathogens d MGE insertions affect antibiotic resistance, virulence, pathogenicity across species

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
109
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(110 citation statements)
references
References 60 publications
1
109
0
Order By: Relevance
“…Microbiome taxonomic profiling is achieved by culturedependent molecular or phenotypic typing or cultureindependent sequencing of taxonomically informative marker genes or whole metagenomic shotgun sequencing from microbiome samples, within or between individuals [11][12][13][14]. Similarly, features and functions of the microbiome can be assessed by gene-level analysis, metabolomics, and assessment of the abundance of gene pathways for microbial metabolic function [15][16][17][18][19][20]. These analyses are typically conducted in the context of human development throughout life or in connection with clinical outcomes [21].…”
Section: Introductionmentioning
confidence: 99%
“…Microbiome taxonomic profiling is achieved by culturedependent molecular or phenotypic typing or cultureindependent sequencing of taxonomically informative marker genes or whole metagenomic shotgun sequencing from microbiome samples, within or between individuals [11][12][13][14]. Similarly, features and functions of the microbiome can be assessed by gene-level analysis, metabolomics, and assessment of the abundance of gene pathways for microbial metabolic function [15][16][17][18][19][20]. These analyses are typically conducted in the context of human development throughout life or in connection with clinical outcomes [21].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, computational approaches are evolving in an effort to support more complete and accurate resistome-mobilome colocalization from short-read metagenomic data (Roodgar et al, 2019;Stalder et al, 2019). Finally and most recently, new approaches have been proposed to increase sensitivity of MGE and AMR discovery and classification (Jiang et al, 2019;Durrant et al, 2020). Though we have expressly highlighted the pervasive issue of cargo sequences in MGE databases, a similar problem likely exists in AMR databases as well.…”
Section: Resultsmentioning
confidence: 99%
“…Here, this was supported by NCTC13441's repertoire of blaTEM and blaOXY genes, contrasting with EC958's variety of blaCMY ones. This reinforced the view that ST131's accessory resistome is shaped by the environment mediated by plasmids, rather than population structure or geographic factors [126], so perhaps tracking plasmids and MGEs in addition to AMR genes [42,127] could assist treatment diagnostics [128]. By combining seven Clade C genome assemblies, then these with 4,064 Clade C assemblies, we found that most (78%) ST131 had >10 Kb of regions similar to plasmid pEK499 and some (9%) had regions with high similarity to IncI1 plasmid pEK204, suggesting either discrete gains of pEK204-like plasmids in each C subclade or its presence in the Clade C ancestral lineage.…”
Section: Operonmentioning
confidence: 82%
“…Like most AMR genes, these are sandwiched by mobile genetic elements (MGEs) on plasmids and thus can be gained by horizontal gene transfer (HGT) [37][38][39] or lost if not beneficial [40][41]. Of nine common bacterial pathogens, E. coli has the most MGEs, including phageassociated ones and transpose (tnpA) genes [42]. Diverse pathogenic bacteria share MGEs [43][44][45] and HGT may worsen nosocomial outbreaks [46][47][48].…”
Section: Introductionmentioning
confidence: 99%